The ethics and governance of stem cell clinical research in India - Tiwari, Shashank Shekhar (2013)
India is rapidly becoming established as a major player in the stem cell sector. However, concerns have been raised about the use of unproven stem cell therapies and the exploitation of parents for cord blood banking. This study aims to explore the nature of stem cell activities, how key stakeholders generate expectations around them and frame the ethical issues they raise, and why the biomedical governance system is unable to regulate these emerging practices. The study involved a survey, documentary analysis and qualitative interviews with key scientists, clinicians, representatives of firms and policymakers.